Conceptualization and Strategic Implementation of Management Information Systems within Islamic Religious Education Institutions - Dhilla Nuraeni Az-Zuhri; Anisa Risma; Melia Nur Padila; Iskandar Mirza (AIM: Journal of Islamic Education Management, 2026)
The rapid advancement of information technology demands that modern educational organizations, including Islamic Religious Education (IRE) institutions, adopt highly structured, effective, efficient, and accountable management paradigms. One crucial intervention to achieve this digital modernization is the strategic application of an integrated Management Information System (MIS). This study aims to provide a comprehensive analysis of the core concepts and operational implementation of MIS within the context of Islamic Religious Education, specifically exploring how foundational Islamic ethical values can be integrated into technological frameworks and analyzing the subsequent practical and theoretical implications. Utilizing a qualitative approach based on descriptive-analytical library research, data were systematically gathered from academic books, peer-reviewed scientific journals, and relevant policy documents. The findings indicate that MIS plays a vital, strategic role in enhancing administrative efficiency, supporting data-based decision-making, and streamlining educational evaluation processes. Crucially, the deliberate integration of core Islamic values—such as tawhid, amanah, justice, and ihsan—establishes a robust ethical infrastructure that distinguishes Islamic educational management from secular models. Ultimately, a value-driven MIS serves as an operational catalyst that successfully transforms conventional Islamic institutions into modernized, professional, and benefit-oriented educational organizations.